CTNI-75. A PILOT CLINICAL TRIAL OF OROTECAN (VAL-413), A NOVEL ORAL DOSAGE FORMULATION OF IRINOTECAN: IMPLICATIONS FOR PEDIATRIC BRAIN TUMORS. (9th November 2020) - Brown, Dennis; Bacha, Jeffrey; Wagner, Lars; Leggas, Markos; Kanekal, Sarath; Lopez, Lorena; Sankar, Neil
Abstract: Tumors of the brain and of the central nervous system (CNS) are the most common solid tumors in children. Intravenous irinotecan hydrochloride (IRN-IV) is approved for the treatment of adult colorectal cancer. IRN-IV is also used off-label in a wide range of treatment regimens for recurrent adult and pediatric tumors including glioblastoma, pediatric glioma and medulloblastoma. Recently, commercially available IRN-IV has been administered orally (IRN-IVPO) in pediatric patients to reduce intravenous administration-related side effects, improve convenience and reduce clinic time and costs. Unfortunately, the poor palatability of this preparation leads to poor compliance, especially in pediatric patients. VAL-413 is novel formulation developed to improve tolerability of oral irinotecan. The current study (NCT04337177) evaluates the safety and pharmacokinetics of VAL-413 administered with temozolomide for treatment of recurrent pediatric solid tumors. METHODS: Up to 20 patients ≥ 1 to ≤ 30 years of age with recurrent pediatric solid tumors will be enrolled. The primary objective is to establish the recommended phase II dose of VAL-413 when given in combination with temozolomide. Secondary objectives include characterization of the pharmacokinetics of VAL-413 vs. IRN-IVPO, evaluating palatability of VAL-413, assessing the toxicity profile of VAL-413 in combination with temozolomide, and assessment of tumor response. Toxicity is evaluated based on CTCAEv5 and tumor response based on RECISTv1.1. An update on the progress of this trial will be presented.